Grammaticalization and phonological characterization of Boholano pronominals - Laput, Daylinda Luz R. (2016)
Strengthening the policy in language education, the Philippine educational system integrates the Mother tongue-based multilingual education to its curriculum. The K to 12 now in full swing includes the use of mother tongues at designated grade levels, expecting learners of Philippine languages to access other languages of world. Boholano is one of the largely spoken varieties of Cebuano, a carried over language of Bol-anons migrating to different places in the archipelago. For the moment, its pronominal system has been deprived of scholarly documentation, thus triggered this study. Dita (2007) stated that pronominals are considered basic vocabulary of any given language and are generally closed-class unaffected by borrowing or code-switching. This paper elucidates the grammar of Boholano pronominals characterizing phonological features of 14 pronouns unique top Cebuano. This explains grammatical functions, together with other known phenomena such as cliticization, phonological variation, inclusivity and exclusivity and person-deixis interface in the Boholano language. Using a 100,000-word list of Binol-anon language and employing an ergative-absolutive analysis, this linguistic study shows sample sentences that illustrate exceptional characteristics of personal pronouns. Using lineal analysis, interpretation shows of a morpheme to morpheme gloss – the text in Boholano or utterance; the interlineal gloss; and its free or literal translation, pointing out evidentiary grammatical features and occasional indexical expressions with emphasis on their phonological variation. Findings of this study revealed that the Boholano language allows enclitization evidenced in cases of inclusivity and exclusivity; indexing person deictical expressions; and 14 of these personal pronouns uniquely and phonologically varies from Cebuano.
Keywords: Boholano language; Mindanao studies